(3eNJUQ GdbGfhf GdbGfhf GdUZjQs - (3GdLZejfj GdNhGQRej, CHh Ydj, TQa GdOjf, eMehO Hf eMeO Hf YeQ, (B618 (3g` (B((3XfG(B)s
(3ChdgG (B:s
(3GdMeO ddg agPG GdeNJUQ eTJed Ydi RHOI eG jLH GSJMVGQg ef UfGYI GdWH hGfJNHJg ef cJH GdCbOejf hQJHJg Ydi YTQI ebGdGJ ; GdebGdI GdChdi s
(3BNQgG (B:s
(3GdaUd GdKGdK YTQ aj GMhGd GdWHN CeG GdGSajOHGLGJ agj edjfI hGdNdjGJ eLaaI hGdeQcHGJ efgG eKd eYJOdI hGddHjSGJ HGQOI hGdeJMOI ef GdejGg GdeYJUQI deGA GdMUQe JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\181s
(3cTa GdXfhf (B2\1312s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs